DEVELOPING STUDENTS' SPEAKING COMPETENCES IN MOTHER LANGUAGE LESSONS IN THE PRIMARY CLASSROOM - Dilbar Daminova (Journals Park Publishing, 2025)
Start in the classrooms mother language lessons students speech competencies in formation the most important stage is considered. Because this at the age of children the language to study very open, speech main laws to occupy ready Therefore, start in the classrooms speech competencies effective develop education process quality determinant main from factors one is considered.
Keywords: Speech competence, elementary education, methodology, interactive methods, writing speech, oral speech, communication culture, creative thinking, innovative technologies, students activity.